TERRESTRIAL COSMOGENIC-NUCLIDE PRODUCTION SYSTEMATICS CALCULATED FROM NUMERICAL SIMULATIONS - Masarik J.; Reedy R.C. (My University, 1995)
Calculations for the production of cosmogenic nuclides in the Earth's atmospheric and in-situ in the surface are reported and discussed. We calculated production rates of 3H, 7Be, 10Be, 14C, and 36Cl in the atmosphere by both galactic cosmic rays and solar protons, and our calculated production rates for 14C agree well with previous results. Production of atmospheric 7Be and 36Cl by solar protons in polar regions is not negligible. Our production rates and depth dependences for in-situ 3He 10Be, 14C, 21Ne, 26Al, and 36Cl agree well with experimental measurements for certain minerals in surface samples. The altitude dependence of in-situ production rates was also calculated.